Analisis Tingkat Kemampuan (Capability Level) Teknologi Informasi Menggunakan Framework Cobit 2019 Domain DSS (Deliver, Service, And Support) Studi Kasus Diskominfo Kota Pematang Siantar - Angga Pratama; Desvina Yulisda; Mutiara Fajar (Jurnal Tika, 2023)
The development of technology and information has impacted organizations, both private and government agencies. The Office of Communication and Informatics of the City of Pematangsiantar is one of the Regional Apparatus Organizations (OPD) with the main task of implementing government affairs in communication and informatics. This research was conducted to find out whether the existing information technology at the Communication and Informatics Office of Pematangsiantar City was running optimally. This study analyzes the capability level (Capability Level) of Information Technology Management in the Pematangsiantar City Communication and Informatics Office using the COBIT (Control Objective for Information and Related Technology) 2019 Domain DSS (Deliver, Service, and Support) framework which focuses on providing support information technology operational services. The data collection methods used are observation and questionnaire methods. Based on data collection through questionnaires from 10 respondents, the average Capability Level Domain DSS result was 3.00 Defined Process, which means that the management of agency information technology uses clearly defined organizational assets and procedures, the process of achieving its goals is now much more organized